THE ROLE OF URBAN MORPHOLOGY IN THE MICROCLIMATE IN A SEMI-ARID CLIMATE CITY - Brandão, Luana Karla de Vasconcelos (2023)
The urbanization process of cities conforms to a typically urban climate, most of the time characterized by the loss of quality of life due to climatic phenomena, such as urban heat islands. The adaptation of the urban form to the local climatic conditions has the potential to compose a sustainable urban environment, with thermal comfort in the open air. The present work took the city of Arapiraca/AL, in order to analyze the relationship between urban morphology and microclimate. From an analytical approach using the ENVI-met software for computer simulation, it was possible to compose four hypothetical models for the hot and dry period. The base model starts from a fraction of the city with a tendency to verticalization, the others vary according to: thermodynamic properties of materials, canyon geometry and vegetation. The results indicated significant thermal effects on urban morphology. The presence of high albedo materials promoted a decrease in air temperature. The orientation of the roads and the geometry of the urban canyon determined the solar access, the number of hours of exposure to direct solar radiation and the use of the winds. The presence of vegetation presented the potential to favor the thermal conditions of the microclimate. It is evident, therefore, the need to insert the study on the urban climate in the urban planning process of cities, in order to promote quality of life for its inhabitants.